IMPLEMENTATION OF THE SEHATI PROGRAM (SEHAT BERSAMA ATASI HIPERTENSI DAN DIABETES) BASED ON THE COMMUNITY AS PARTNER MODEL IN RW 12, SUKOREMBUG, BATU CITY - Setyoadi, Setyoadi; Badriah, A. Sobihatul; Syarifah, Aisyah Nur; Fakhirah, Arin; Asyawa, Balqist; Putri, Andra; Raharjo, Charina Lorenza; Amanda, Febrina; Famela, Iputa Melany; Kharismayani, Kadek Dwi; Safira, Nisrina Naural; Azzahra, Putri Nur Fadhillah; Salsabila, Rizal; Qushoyya, Sayyidah Mumtazatul; Assalaika, Widya Rahma; Wijayanti, Yuyun Dwi (Caring: Jurnal Pengabdian Masyarakat, 2025)
Hypertension and type 2 diabetes mellitus are major non-communicable diseases that continue to pose serious public health challenges due to unhealthy lifestyles and low health literacy. This community service activity aimed to empower residents of RW 12, Dusun Sukorembug, Kota Batu through the SEHATI program (Sehat Bersama Atasi Hipertensi dan Diabetes) based on the Community-as-Partner model. Implemented from April to May 2025, the program involved 42 households and included interventions across five pillars: SEHATI PEDULI (home visits and early detection), SEHATI INFO (health education via media), SEHATI RASA (use of traditional herbal drinks), SEHATI TENANG (stress management using hypnosis and herbal foot soaks), and SEHATI AKTIF (physical exercises). Post-intervention evaluations showed increased health knowledge (71.6% for hypertension and 74.6% for diabetes), 100% screening coverage, 85.7% participation in physical activity, and 76.2% medication adherence, along with improved blood pressure and glucose levels. The success of the program was supported by active community participation and integration with local events, demonstrating that a participatory, culturally sensitive approach is effective in improving community health outcomes related to hypertension and diabetes